Crecimiento, mortandad y sobrevivencia de la especie Swietenia macrophylla King. “caoba” de la plantación N° 08 del CIEFOR - Puerto Almendra, Loreto – Perú. 2021 - Garay Dinis, Danika Journeth (2022)
The study was carried out in Forest Parcel No. 06 of 1 ha in Ciefor - Puerto Almendras, evaluating 200 Swietenia macrophylla plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by band 2 with a value of 0,82 mm between the first and last evaluation. Likewise, in height the greatest increase was presented by band 2 with a value of 25.95 cm. The Chi square test indicates that there is a significant difference between the averages of increase in diameter - height and the bands (p-value = 0.00 <α = 0.05. The survival of cedar plants varies between 95% to 100% survival, while mortality reached 5%. The highest mortality was presented by band 9 with 6 dead plants, which represents 30% of the dead plants. The highest number of plants presented GOOD quality with 181 seedlings that represents 90,952% of the total, followed by REGULAR quality with 14 live individuals that indicates 7,04 % and, finally, the least amount of individuals were observed in BAD quality with 4 seedlings that represented 2,01 % of the total. At a general level in the experiment Good quality (band 1, 3, 5, 6, 9 and 10) was recorded for the Swietenia macrophylla seedlings at the end of the study. Similar studies are needed with other native forest species in CIEFOR - Puerto Almendras.